Monetary Policy Rate and Economic Growth in Nigeria - Ovat, Okey O.; Ishaku, Rimamtanung Nyiputen; Ugbaka, Malachy Ashywel; Ifere, Eugene Okoi (International Journal of Economics and Financial Issues, 2022)
This study empirically evaluated the effect of monetary policy rate (MPR) on Nigeria’s economic growth using annual data spanning 2006 - 2020. The technique adopted in this paper is a simultaneous equation model using two Stage Least Squares (2SLS). Variables of interest were Broad money supply as a ratio of GDP (M2/GDP), Credit to the private sector as a ratio of GDP (CPS/GDP), Cash reserve ratio (CRR), Liquidity ratio (LQR), and Lending interest rate (LIR). The preliminary unit root test revealed stationarity at first difference. The weak instrument test result shows a robust instrument at 10 and 20 per cent. While the residual result indicates an absence of heteroskedasticity in the model. The findings revealed that monetary policy rate has a negative but significant effect on economic growth, Real Exchange Rate (REXR) has an inverse relationship and significant effect on economic growth while inflation (INFL) has a negative and insignificant impact on economic growth. Given that monetary policy rate significantly impacts economic growth in Nigeria, the paper recommended that the Central bank of Nigeria should ensure that the fixing of the monetary policy rate is such that it enables the flow of credit in the desired direction to boost investment and economic activities in the economy; by identifying the Monetary Policy Rate threshold that is suitable for price stability, investment and output growth.